Formative assessment : making it happen in the classroom - Heritage, Margaret (Corwin, 2010)
Formative assessment allows teachers to identify and close gaps in student understanding and move learning forward. This research-based book helps educators develop the knowledge and skills necessary to successfully implement formative assessment in the classroom. Margaret Heritage walks readers through every step of the process and offers specific examples to illustrate the implementation of formative assessment across a range of subject areas and grade levels. This book explains how to: Clearly articulate learning progressions, learning goals, and success criteria. Select strategies for assessment and provide quality feedback. Engage students in self-assessment and self-management. Create a classroom environment that values feedback as part of the learning process With guidance for school administrators who want to promote schoolwide implementation, Formative Assessment helps educators effectively target their teaching and improve learning for all students.- Resumé vydavatel